Analysis on the Changes of Functional Groups after Coal Dust Explosion at Different Concentrations Based on FTIR and XRD. Issue 14 (26th October 2021) - Li, Xiaoliang; Liu, Zhentang; Qian, Jifa; Zhou, Dong
ABSTRACT: In this study, experiments were performed on coal dust explosion (CDE) at different concentrations by using a 20 L spherical explosion device. Besides, the raw coal and solid residues of CDE were subjected to FTIR and XRD analyses. The aims are to investigate the changes of functional groups after CDE at different concentrations, the relationship between functional group consumption rate and explosion characteristic parameters, and the changes of inorganic minerals. The results show that during the CDE, various functional groups are consumed to varying degrees. Among the groups, the consumption of oxygen-containing functional groups is the most, followed by those of hydroxyl groups and aliphatic hydrocarbons, and that of aromatic hydrocarbons is the least. When the coal dust concentration is greater than 200 g/m 3, the functional group consumption rate exceeds 50%; when the coal dust concentration exceeds 500 g/m 3, the functional group consumption rate exceeds 90%. The total consumption of functional groups is positively correlated with the explosion pressure P m, the growth rate of explosion pressure (d p /d t )m, the flame propagation velocity V F and the impulse I during the CDE experiments. Compared with raw coal, solid residues of CDE possess an increased content of minerals. The absorption peak area of minerals reaches a maximum of 10.28 (about 10 times of that for the raw coal) under the concentration of 700 g/m 3 . The main mineral components vary before and after the CDE. The main mineral components in the raw coal are quartz and kaolinite, while the main mineral components in the solid residues after CDE are quartz, calcium zeolite, wollastonite and magnesium oxide.